2008
DOI: 10.1177/0961203307085670
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic capacity correlates to self-assessed physical function but not to overall disease activity or organ damage in women with systemic lupus erythematosus with low-to-moderate disease activity and organ damage

Abstract: The present aim is to investigate the relationships between aerobic capacity and disease activity, organ damage, health-related quality of life (HRQL) and physical activity in 34 women with systemic lupus erythematosus (SLE) with low-to-moderate disease activity and organ damage. Mean age was 51 (SD 10) years, disease duration 17 (SD 11) years. Aerobic capacity (maximal oxygen uptake/VO2 max) was measured with a bicycle ergometer exercise test. Overall disease activity was assessed with Systemic Lupus Activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…These data are in line with previous studies that have found that adults with SLE have diminished muscle and aerobic capacity compared to age-matched controls [8, 9]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are in line with previous studies that have found that adults with SLE have diminished muscle and aerobic capacity compared to age-matched controls [8, 9]. …”
Section: Discussionsupporting
confidence: 93%
“…SLE patients may experience difficulties when trying to become more active; for example, adults with SLE are known to have decreased cardiovascular endurance, lower muscle strength, and lower lean muscle mass compared to age-matched controls [8, 9]. Children with SLE are known to have higher fat mass compared to their peers; lower lean muscle mass in these children has been associated with complications such as vertebral fractures [1014].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown correlations between the physical functioning subscale of the SF-36 and the objective aerobic capacity level of respondents. For example, in the study of Boströ m and colleagues a significant correlation between aerobic capacity and self-assessed physical function according to the SF-36 was found (r ¼ 0.49, P < 0.01) (Boströ m et al, 2008). Comparable results were found in the study of Stewart et al (2003), with a significant correlation (r ¼ 0.33, P < 0.01) reported.…”
Section: Introductionmentioning
confidence: 91%
“…5,6,8 Interestingly, in lupus patients the reduction in aerobic capacity was also associated with a poor health-related quality of life. 16 Moreover, lower levels of aerobic capacity indexes in the general population are associated with increased cardiovascular risk and mortality. 17 Thus, these variables can be important tools in evaluation of risks in PAPS patients.…”
Section: Discussionmentioning
confidence: 99%